2017
DOI: 10.3389/fpls.2017.01440
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Evaluation of Reference Genes for Quantitative RT-PCR Analysis during Tomato Fruit Development

Abstract: Gene expression analysis in tomato fruit has drawn increasing attention nowadays. Quantitative real-time PCR (qPCR) is a routine technique for gene expression analysis. In qPCR operation, reliability of results largely depends on the choice of appropriate reference genes (RGs). Although tomato is a model for fruit biology study, few RGs for qPCR analysis in tomato fruit had yet been developed. In this study, we initially identified 38 most stably expressed genes based on tomato transcriptome data set, and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…1b). Previous studies have reported that the expression level of reference genes is not always stable under all experimental conditions [2730] and that mRNA expression levels varied among several housekeeping genes [40, 41]. Here these factors were confirmed in different tissues of H. brevisubulatum under various abiotic stresses and hormone treatments (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…1b). Previous studies have reported that the expression level of reference genes is not always stable under all experimental conditions [2730] and that mRNA expression levels varied among several housekeeping genes [40, 41]. Here these factors were confirmed in different tissues of H. brevisubulatum under various abiotic stresses and hormone treatments (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…In order to interpret RT-qPCR data accurately and reliably, appropriate reference genes are essential. Many reports in several plant species such as Arabidopsis ( Arabidopsis thaliana ), tomato ( Solanum lycopersicum ) and grape ( Vitis vinifera ) have shown the importance and need to validate appropriate reference genes for normalizing RT-qPCR data in different tissues, developmental stages or experimental conditions 22 27 . To date, only the housekeeping gene ACT was used as a reference gene in S .…”
Section: Discussionmentioning
confidence: 99%
“…BA-124 and BA-128 are normal lines derived from BC2S1 plants generated by continued backcrossing of 06-790 to H1706. Note: To normalize the expression data, the SIFRG27 (Solyc06g007510) gene was used as the internal control (Cheng et al, 2017). The bars represent the standard deviation.…”
Section: The Promoter Sequence Deletion Down-regulates the Expressionmentioning
confidence: 99%